How Useful Is the Concept of Skills Mismatch? - Seamus McGuinness; Konstantinos Pouliakas; Paul Redmond (Institute of Labor Economics (IZA), 2017)
The term skill mismatch is very broad and can relate to many forms of labour market friction, including vertical mismatch, skill gaps, skill shortages, field of study (horizontal) mismatch and skill obsolescence. In this paper we provide a clear overview of each concept and discuss the measurement and inter-relatedness of different forms of mismatch. We present a comprehensive analysis of the current position of the literature on skills mismatch and highlight areas which are relatively underdeveloped and may warrant further research. Using data from the European Skills and Jobs Survey, we assess the incidence of various combinations of skills mismatch across the EU. Finally, we review the European Commission's country specific recommendations and find that skills mismatch, when referring to underutilised human capital in the form of overeducation and skills underutilisation, receives little policy attention. In cases where skills mismatch forms part of policy recommendations, the policy advice is either vague or addresses the areas of mismatch for which there is the least available evidence.
Keywords: J24; I20; I28; 330; skill mismatch; overeducation; skill shortages; skill gaps; European skills and jobs survey; policy